The graph is shown in figure below
The Solution Set is (-2,-3)
Step-by-step explanation:
We need to graph the equations and writ the solution.
For graphing we need to find the values of x and y.
For that, we need to solve the given equations:
![2x + 1 = y\\-4x + 6y = -10](https://tex.z-dn.net/?f=2x%20%2B%201%20%3D%20y%5C%5C-4x%20%2B%206y%20%3D%20-10)
Let:
![2x + 1 = y\,\,\,eq(1)\\-4x + 6y = -10\,\,\,eq(2)](https://tex.z-dn.net/?f=2x%20%2B%201%20%3D%20y%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C-4x%20%2B%206y%20%3D%20-10%5C%2C%5C%2C%5C%2Ceq%282%29)
We can solve this by using Substitution Method.
Putting value of y of eq(1) into eq(2) and finding value of x:
![2x + 1 = y\,\,\,eq(1)\\-4x+6(2x+1)=-10\\-4x+12x+6=-10\\8x+6=-10\\8x=-10-6\\8x=-16\\x=-16/8\\x=-2](https://tex.z-dn.net/?f=2x%20%2B%201%20%3D%20y%5C%2C%5C%2C%5C%2Ceq%281%29%5C%5C-4x%2B6%282x%2B1%29%3D-10%5C%5C-4x%2B12x%2B6%3D-10%5C%5C8x%2B6%3D-10%5C%5C8x%3D-10-6%5C%5C8x%3D-16%5C%5Cx%3D-16%2F8%5C%5Cx%3D-2)
So, value of x = -2
Now put value of x in eq(1) to find value of y:
![2x + 1 = y\\2(-2)+1=y\\-4+1=y\\y=-3](https://tex.z-dn.net/?f=2x%20%2B%201%20%3D%20y%5C%5C2%28-2%29%2B1%3Dy%5C%5C-4%2B1%3Dy%5C%5Cy%3D-3)
So, value of y = -3
Plotting on graph: x=-2 and y = -3
The graph is shown in figure below
The Solution Set is (-2,-3)
Keywords: graph the equations
Learn more about Graphing Equations at:
#learnwithBrainly